2020
DOI: 10.1177/0022343320961835
|View full text |Cite
|
Sign up to set email alerts
|

Contesting narratives of repression: Experimental evidence from Sisi’s Egypt

Abstract: Authoritarian regimes frequently attempt to justify repression by accusing their opponents of violent behavior. Are such claims successful at persuading the public to accept state-sponsored violence, and can these claims be contested effectively by human rights organizations seeking to publicize evidence contradicting the regime’s narrative? To evaluate these questions, we conducted a survey experiment in Egypt using Facebook advertisements to recruit respondents safely. The experiment evaluates the persuasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…In the same research, Williamson dan Malik [25] also explains that authoritarian regime often tries to justify repression by accusing their opposition of using violence. This also happens in Indonesia, where the government insisted that there is a 'specific and abnormal' situation which requires security approach due to 'the Papuans' characteristic' without ever specifically explaining said situation which in turn makes it difficult to trust since demonstrations (which then leads to riots) are common in various regions in Indonesia and is not a defined characterizations of Papuans alone, as mentioned by Samuel Abrijani Pengerapan, Director General of Informatics Application in MoCI, and Albert Rudolf Rodja Head of Papua Regional Police Force in Judgement No.230/G/TF/2019/PTUN-JKT State Administrative Court.…”
Section: The Use Of National Security As a Policy Narrative As A Form...mentioning
confidence: 95%
See 1 more Smart Citation
“…In the same research, Williamson dan Malik [25] also explains that authoritarian regime often tries to justify repression by accusing their opposition of using violence. This also happens in Indonesia, where the government insisted that there is a 'specific and abnormal' situation which requires security approach due to 'the Papuans' characteristic' without ever specifically explaining said situation which in turn makes it difficult to trust since demonstrations (which then leads to riots) are common in various regions in Indonesia and is not a defined characterizations of Papuans alone, as mentioned by Samuel Abrijani Pengerapan, Director General of Informatics Application in MoCI, and Albert Rudolf Rodja Head of Papua Regional Police Force in Judgement No.230/G/TF/2019/PTUN-JKT State Administrative Court.…”
Section: The Use Of National Security As a Policy Narrative As A Form...mentioning
confidence: 95%
“…Though the state's concern for national security during the demonstrations on August-September 2019 was a valid one, we also consider Williamson and Malik's [25] thoughts that national security is often used to justify repressive actions; in their research, they explained that as long as the state (security apparatus) controls narrations to justify a policy, the people are most likely to support the state's policy, but if said narrations are contested by other organizations which brought upon human rights perspective into their contra-narration, people's opinion will change. This description of Williamson and Malik's research fits perfectly to this case.…”
Section: The Use Of National Security As a Policy Narrative As A Form...mentioning
confidence: 99%
“…In the polar opposite of this thought will be the research done by Williamson and Malik (2020), who found that authoritarian regime often justifies repression by accusing their opposition of violence which prompts the regime to use security approach for the safety of the people. This research found that as long as the state controlled the narration surrounding a justification of murder, people tend to support their (the state's) decision.…”
Section: National Security: the Duty To Maintain Public Order Or A Po...mentioning
confidence: 99%
“…These two thoughts exist in the polar opposite on how to understand the concept of national security. In this research, I am using the concept of national security as the base of the state's action without discounting Williamson and Malik's (2020) view when analyzing the contra narration of Internet Shutdown at Papua and West Papua in 2019.…”
Section: National Security: the Duty To Maintain Public Order Or A Po...mentioning
confidence: 99%
“…Paid advertisements running on platforms such as Facebook and Instagram offer a unique opportunity for researchers, who need quick and cost-effective access to a pool of online survey participants. During the last few years, scholars have used Facebook Ads for recruitment in countries all around the world, such as Egypt (Williamson & Malik, 2020), Indonesia (Ananda & Bol, 2020), Kenya and Tanzania (L. R. Rosenzweig & Zhou, 2021), Thailand (Jäger, 2017), Turkey (Elci, 2021), and Uruguay (Bentancur et al, 2019). The Coronavirus pandemic has further revealed the potential of Facebook for scholarly research.…”
Section: Introduction: Potentials and Pitfallsmentioning
confidence: 99%